Modeling and simulation of a cooled CPC-ORC coupled system: Performance analysis. (November 2022) - Carlini, Maurizio; Rotondo, Mirko; Marcantonio, Vera; Pierini, Daniele; Mennuni, Andrea
Abstract: The aim of reducing exploitation of the earth leads to the development of Renewable Energy Sources (RES). A technology that achieves this purpose using the solar energy is the Compound Solar Concentrator, able to increase the conveyance of the sun's rays onto the solar cells. In this work this technology is equipped with a Coil Cooling System, to cool the system by improving the conversion efficiency. The heat absorbed by the cooling water represents usable energy in an Organic Rankine Cycle (ORC) system. The first part of the work is based on transient numerical simulations of the cooled Compound Parabolic Concentrator (CPC) with COMSOL Multiphysics (CM) software. The performance parameters show that after about n.20 models the improvements are contained reaching a thermal equilibrium. The selected number of cooled CPCs is n.20, reaching a temperature of the outlet water from coils of 50 °C and a flow rate composed of n.2 coils of 1.2 l/min. Exploiting this outlet water, an ORC technology is coupled from a simulation point of view with the cooled CPC, making it possible to obtain an electric and thermal efficiency of 11.73% and 60.30% respectively with a pump pressure of 20 bar.